Application of a semi‐empirical dispersion correction for modeling water clusters. Issue 2 (20th October 2018) - De Silva, Nuwan; Adreance, Matthew A.; Gordon, Mark S.
Abstract : The Grimme‐D3 semi‐empirical dispersion energy correction has been implemented for the original effective fragment potential for water (EFP1), and for systems that contain water molecules described by both correlated ab initio quantum mechanical (QM) molecules and EFP1. Binding energies obtained with these EFP1‐D and QM/EFP1‐D methods were tested using 27 benchmark species, including neutral, protonated, deprotonated, and auto‐ionized water clusters and nine solute–water binary complexes. The EFP1‐D and QM/EFP1‐D binding energies are compared with those obtained using fully QM methods: second‐order perturbation theory, and coupled cluster theory, CCSD(T), at the complete basis set (CBS) limit. The results show that the EFP1‐D and QM/EFP1‐D binding energies are in good agreement with CCSD(T)/CBS binding energies with a mean absolute error of 5.9 kcal/mol for water clusters and 0.8 kcal/mol for solute–water binary complexes. © 2018 Wiley Periodicals, Inc. Abstract : In the field of molecular modeling, explicit representation of water as a solvent is crucial because implicit solvent methods do not provide the same deep insight into many systems of interest. The dispersion‐corrected effective fragment potential (EFP1‐D) method can accurately predict the structures and binding energies in the water–water and water‐solute complexes including neutral, protonated, deprotonated, and auto‐ionized species. The EFP1‐D and QM/EFP1‐D binding energies of the test sets are compared against CCSD(T)/CBS.